Retrospective analysis of the quality of root canal filling according to the data of cone-beam computed tomography - A. A. Adamchik; V. V. Dorogan; E. S. Zaporozhskaya-Abramova; V. V. Tairov; V. A. Ivashchenko; K. D. Kirsh; S. A. Korovashkin (LLC "Endo Press", 2022)
Aim. Analysis of complications in the treatment of complicated caries.Materials and methods. Cone beam computed tomography results of 200 patients aged 21 to 64 years. The teeth were divided into frontal and chewing groups. The quality of the performed endodontic treatment was assessed.Results. During the analysis of the results of cone-beam computed tomography, the following complications of endodontic treatment were revealed: incomplete obturation of the root canal, removal of material beyond the apex of the tooth root, missed root canal, fracture of the instrument in the root canal. The regularity of their frequency was established, depending on the part of the jaw in which the tooth was located.Conclusions. Conducting cone-beam computed tomography during diagnosis, during treatment, will eliminate complicationsassociated with a lack of diagnostic imaging, effectively assess the success of the treatment for timely action.